#TITLE_ALTERNATIVE# - WIBAWA (NIM 25306019), KRESNA
A study of health risk assessment among workers exposed to silica dust was conducted from January to February 2008. The objective was to find the risk of working with silica dust. The health effect was represented by the lung volume, taking FEV1.0 as a parameter. To evaluate the danger/hazard working with silica dust, the hazard index (HI) was measured, for which the average daily intake of dust (ADD) need to be measured using personal exposimeters, and to find reference dose (RfD), the percentage of free silica was examined within the dust using X-ray diffraction method and both ADD and % free silica were then used to calculate the RfD in mg/m3 = 10 / (2+% free silica). Dose-response assessment was conducted between dust concentration inhaled and their corresponding FEV1.0 to find consistency of the cause-effect relationship. To find the relative risk (RR) of developing lower FEV1.0 if exposed to free silica, epidemiologic method was used to compare the dose and response between the exposed and the non-exposed workers. The resulting average HI for exposed workers was 30.74 as compared to the non exposed of 0.38. The highest HI of 81.82 was found among those working in the sand preparation process (Cor 2), followed by sand casting department with a HI of 48.79 (Cor 2), furan and disamatic line (Cor 1) of 4.96 and 2.26 respectively. The most potential process exposing workers to silica was at shake-out disamatic and furan line having crystalline silica concentrations of 0.133 mg/m3 and 0.460 mg/m3 respectively. A strong association was found between the ADD and the lowering of FEV1.0 as shown by the R2 value of 0.94. The dose-response curve also showed a consistent relationship between dose and FEV1.0. The RR of HQ was unaccountable (~), meaning that silica dust is very dangerous to health, even if the effective TLV were still being met. As the risk for developing a lower FEV1.0 when exposed to silica dust was 5.68. It is therefore recommended that if possible silica dust should be substituted with less/non dangerous materials. Periodic health conditions of worker should be monitored for early signs of silicosis and/or abnormal lung volumes and/or lung X-ray photos, considering that silicosis is a progressive disease.